Edukasi Manfaat Lilin Aromaterapi Anti Nyamuk Di Desa Meunasah Deyah Aceh Besar - Hayati, Rahmah; Isfanda, Isfanda; Hidayah , Hidayah; Adila, Tasya (Nawadeepa: Jurnal Pengabdian Masyarakat, 2025)
Demam Berdarah Dengue (DBD) is an infectious disease induced the dengue virus from the genus Flavivirus, family Flaviviridae, and transmitted the Aedes aegypti mosquito. This disease was known as DBD wherein an endemic disease especially in tropical Indonesia country. Using the natural ingredients as mosquito repellent could be an alternative reduce to used of the chemical mosquito repellent. The purpose of this dedication was to provide knowledge about DBD, and to introduce the aromatherapy candles with lemongrass and cinnamon as natural mosquito repellent ingredients as botanical insecticides. The method was used to direct demonstration in the Meunasah Deyah Village Community, Aceh Besar Regency. The observations before and after participants were given educated to made the aromatherapy candles as an alternative natural mosquito repellent ingredient to a renewable innovation, especially that economically profitable in the future. The aromatherapy candles were not damage the environment or constrain the health problems. Furthermore, the aromatherapy candles contained the compound of citronellol and geraniol established damage the brain nerves of DBD mosquitoes. The aromatherapy candle was provide an anti-stress, and calming the aroma sensation for humans. This innovation was easy for people to made, and it was not harm the skin and induced to side effects for humans and livestock community.